QUALITY AND SAFETY EVALUATION OF CHICKEN SHAWARMA IN CHENNAI - D. Raghu; M. Parthasarathy; S. Sangavi; G. Sarathchandra (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Shawarma is a popular ready-to-eat food consumed by a diverse spectrum of populations in Chennai and other parts of India. The consumption of shawarma has dramatically increased in recent years. Although it is consumed by many people, especially the younger generation, the quality and safety of the shawarma are questionable. In this study, 10 chicken shawarma samples were purchased from local restaurants in Chennai city to assess their quality and safety by estimating rancidity profile in terms of free fatty acid (FFA) and peroxide value, histamine content, and microbial contamination. The results revealed that the percentage of FFA and peroxide values ranged from 1.41±0.99 to 7.05±1.73 and 2±0.57 to 14±1.47 meq/kg, respectively. Among the tested samples, 30% showed the presence of a significant level of histamine content (1.7–7 mg/100g). The biochemical characterization of bacterial isolates from shawarma samples revealed the presence of contamination by Salmonella enteric sub sp. enterica, Escherichia coli STEC 367, Listeria monocytogenes, and Listeria innocua. Further, these isolates were also confirmed by PCR by amplifying a 284 bp invA gene fragment for Salmonella sp., an 884 bp uspA gene fragment for E. coli, and a 457 bp iap gene fragment for Listeria sp. The findings of this study emphasize the significance of safety monitoring for ready-to-eat foods.